Assessment of cardiorespiratory fitness in medical students using the Queen’s College Step Test: A gender-based analysis of VO2max - Prajapati, Rajesh; Amatya, Neebha; Shrestha, Ripti; Rana Magar, Rajab; Amatya, Mrigendra (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: VO2max, a measure of the maximum oxygen uptake during physical exertion, is a critical indicator of cardiovascular fitness. Evaluating VO2max in young adults helps in understanding their fitness levels and guiding improvements. This study aimed to assess normal VO2max levels and investigate the relationships between oxygen saturation (SpO2) and VO2max, as well as between blood pressure and VO2max, in both male and female participants. Methods: A total of 93 students (45 males, 48 females) aged 18 to 25 years from Gandaki Medical College, Pokhara, were selected through simple random sampling. VO2max was estimated using the Queen’s College Step Test (QCT), a widely accepted indirect method to assess cardiorespiratory fitness. QCT provides a convenient way to evaluate maximum oxygen uptake in a non-laboratory setting. Results: The mean VO2max for male participants was 62.00±8.77 ml/kg/min, while for females, it was 41.79±3.18 ml/kg/min. Males exhibited significantly higher VO2max values compared to females (p<0.001). Both diastolic blood pressure (p = 0.013) and SpO2 (p < 0.001) were found to have a significant influence on VO2max in female but not changed in the male. Conclusions: This study confirms that gender-related differences in cardiovascular fitness exist, with males generally showing higher endurance levels compared to females. The lower VO2max values observed in females were primarily associated with variations in SpO2 and diastolic blood pressure. These findings highlight the importance of considering physiological variables such as oxygen saturation and blood pressure in the assessment of female cardiorespiratory fitness.